When Positive Ischemic Response on Treadmill Test Implies Otherwise: One Overlooked Pitfall on TMT - Rifanda, Dmitri Muhammad; Parama, M. A. L.; Putra, Teuku Muhammad Haykal; Widodo, Wishnu Aditya (Jurnal Kardiologi Indonesia, 2025)
In “When Positive Ischemic Response on Treadmill Test Implies Otherwise: One Overlooked Pitfall on TMT” (Indonesian Journal of Cardiology, 43(1), 30-6. https://doi.org/10.30701/ijc.1197), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1197. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1197